Responding to global challenges in food, energy, environment and water: risks and options assessment for decision-making - Grafton, R. Quentin; McLindin, M.; Hussey, K.; Wyrwoll, P.; Wichelns, Dennis; Ringler, Claudia; Garrick, D.; Pittock, J.; Wheeler, S.; Orr, S.; Matthews, Nathaniel; Ansink, E.; et al. (Wiley, 2016)
We analyse the threats of global environmental change, as they relate to food security. First, we review three discourses: (i) ‘sustainable intensification’, or the increase of food supplies without compromising food producing inputs, such as soils and water; (ii) the ‘nexus’ that seeks to understand links across food, energy, environment and water systems; and (iii) ‘resilience thinking’ that focuses on how to ensure the critical capacities of food, energy and water systems are maintained in the presence of uncertainties and threats. Second, we build on these discourses to present the causal, risks and options assessment for decision-making process to improve decisionmaking in the presence of risks. The process provides a structured, but flexible, approach that moves from problem diagnosis to better risk-based decision-making and outcomes by responding to causal risks within and across food, energy, environment and water systems.